"I still feel so lost": experiences of women receiving SANE care during the year after sexual assault. Issue 4 (3rd July 2021) - Buchbinder, Mara; Brassfield, Elizabeth R.; Tungate, Andrew S.; Witkemper, Kristen D.; D'Anza, Teresa; Lechner, Megan; Bell, Kathy; Black, Jenny; Buchanan, Jennie; Reese, Rhiannon; Ho, Jeffrey; Reed, Gordon; et al.
Abstract: Objective: Emergency caregivers provide initial care to women sexual assault (SA) survivors. An improved understanding of the issues facing this population can aide emergency care practitioners in providing high quality care. The goal of this study was to share the experiences of women SA survivors with the emergency care practitioners that care for them. Methods: English‐speaking adult women (n = 706) who received SA Nurse Examiner (SANE) evaluation within 72 hours of SA at 1 of 13 geographically distributed sites were enrolled in a prospective, longitudinal multi‐site observational study. We qualitatively analyzed responses to the open‐ended question: "What do you think is most important for researchers to understand about your experience since the assault?" asked 1 week, 6 weeks, 6 months, and 1 year after enrollment. Results: Themes from responses (n = 1434) from 590 women (84% of study sample) fell into 12 broad categories: daily life, justice, medical, and social services, mental health, physical health, prior trauma, recovery, romantic relationships, safety, self, shame, and social interactions. Responses demonstrated that the assault permeates many aspects of assault survivors' daily lives. Conclusions: Qualitative analyses of open‐ended responses from a large cohort of women SA survivors receiving SANE care highlight the challenges for survivors and can increase understanding among the emergency care practitioners who care for them. The authors propose a brief acronym to help emergency care practitioners recall important messages for SA survivors.